Higher Non-processed Red Meat Consumption Is Associated With a Reduced Risk of Central Nervous System Demyelination - Black, Lucinda J.; Bowe, Gabrielle S.; Pereira, Gavin; Lucas, Robyn M.; Dear, Keith; van der Mei, Ingrid; Sherriff, Jill L.; , the Ausimmune Investigator Group; Chapman, Caron; Coulthard, Alan; Dear, Keith; Dwyer, Terry; et al. (Frontiers in Neurology, 2019)
The evidence associating red meat consumption and risk of multiple sclerosis is inconclusive. We tested associations between red meat consumption and risk of a first clinical diagnosis of central nervous system demyelination (FCD), often presaging a diagnosis of multiple sclerosis. We used food frequency questionnaire data from the 2003-2006 Ausimmune Study, an incident, matched, case-control study examining environmental risk factors for FCD. We calculated non-processed and processed red meat density (g/1000 kcal/day). Conditional logistic regression models (with participants matched on age, sex and study region) were used to estimate odds ratios (ORs), 95% confidence intervals (95% CI) and p values for associations between non-processed (n=689, 250 cases, 439 controls) and processed (n=683, 248 cases, 435 controls) red meat density and risk of FCD. Models were adjusted for history of infectious mononucleosis, serum 25-hydroxyvitamin D concentrations, smoking, race, education, body mass index and dietary misreporting. A one standard deviation increase in non-processed red meat density (22 g/1000 kcal/day) was associated with a 19% reduced risk of FCD (AOR=0.81; 95%CI 0.68,0.97; p=0.02). When stratified by sex, higher non-processed red meat density (per 22 g/1000 kcal/day) was associated with a 26% reduced risk of FCD in females (n=519; AOR=0.74; 95%CI 0.60, 0.92; p=0.01). There was no statistically significant association between non-processed red meat density and risk of FCD in males (n=170). We found no statistically significant association between processed red meat density and risk of FCD. Further investigation is warranted to understand the important components of a diet that includes non-processed red meat for lower FCD risk.